The Case of Tito and Soma Mukhopadhyay: Factitious Heroism by Proxy, Factitious Heroism, and Revealing the Deception Thereof for the Future of Autism Treatment - Dan Howitt (International Society of Philosophy and Cosmology, 2021)
I reveal the masterful multifaceted communicative fraud that Soma Mukhopadhyay has engaged in with her profoundly autistic son Tito since 2000 on an array of major television programs, and in the presence of an array of scientists, physicians, and autism organization leaders who studied them, and which has not been observed by anyone else. Soma has deceived the public that her son has a normal if not advanced neurology and mind, and that all profoundly autistic persons may as well. She devised a variation of the treatment method and educational method that is referred to as Facilitated Communication, and refers to her method as the Rapid Prompting Method. By my having revealed the intricacy of the communicative fraud that she engages in with Tito, (a) the past, current, and future treatment methods and educational methods for autistic persons may be assessed more carefully by scientists, physicians, journalists, autism organization leaders, and others, and (b) the ways that autistic persons are conceived of may be proceeded with more carefully. I do not intend for my observational work, and ensuing conceptual work, to demonstrate to others that the particular fraud that Soma engages should be monitored for, but rather. that claims of, and demonstrations of, treatment methods and educational methods for autism be acutely visually and auditorily observed, such that the innumerable kinds of fraud that may be occurring are observed. The assessment of treatment methods and educational methods for autism with preexisting methodologies will likely result, as it did of Tito and Soma, in highly surreptitious fraud being overlooked, and perpetuated; and this entails the proliferation of mass deception.